2010
DOI: 10.1063/1.3486014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of AlGaAs energy barriers on InAs/GaAs quantum dot solar cells

Abstract: We have studied the effects of AlGaAs energy barriers surrounding self-assembled InAs quantum dots in a GaAs matrix on the properties of solar cells made with multiple quantum dot layers in the active region of a photodiode. We have compared the fenced dot samples with conventional InAs/ GaAs quantum dot solar cells and with GaAs reference cells. We have found that, contrary to theoretical predictions, the AlGaAs fence layers do not enhance the transport properties of photogenerated carriers but instead suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 10 publications
1
20
0
Order By: Relevance
“…The QDSC has a 5.8% increase of the short‐circuit current density (Jsc) and a 16% decrease of the Voc compared with the reference cell, leading to an overall reduction in efficiency from 14.3% to 12.3%. This result is consistent with other reports , and the increased Jsc of the QDSC further indicates that the QDs are of high optical quality. The room temperature spectral response and photoluminescence spectrum are plotted together in Figure .…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The QDSC has a 5.8% increase of the short‐circuit current density (Jsc) and a 16% decrease of the Voc compared with the reference cell, leading to an overall reduction in efficiency from 14.3% to 12.3%. This result is consistent with other reports , and the increased Jsc of the QDSC further indicates that the QDs are of high optical quality. The room temperature spectral response and photoluminescence spectrum are plotted together in Figure .…”
Section: Resultssupporting
confidence: 93%
“…Sablon et al . reported that additional AlGaAs barrier layers surrounding QDs inhibited the extraction of carriers from bound states. The use of thin high bandgap barrier layers surrounding QD layers can have the added property of suppressing sub‐bandgap 2D wetting layer transitions, thus allowing only the generation of 0D QD sub‐bandgap transitions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations show that the maximum power conversion efficiency can be theoretically as high as 45% for a QD solar-cell that has 10~20 layers of indium-arsenide (InAs) QDs encapsulated by an aluminum-gallium-arsenide (AlGaAs) high potential barrier fence under AM1.5 spectral radiation. 4) Although experimental studies [5][6][7][8] at the current stage show lower efficiencies, mostly ranging from 7 to 12%, another theoretical study predicts that it can be as high as 25~50% depending on the precise control of QD dimension and gallium content in In x Ga 1-x N/GaN QD IB solar-cells.…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductor quantum dots (QDs) are considered as a candidate system to form such IBs because of the discrete energy levels introduced by the 3-dimensional confinement of QDs. Several QD systems have been investigated over the past decade [4]- [9] where the most well-studied material system for IBSC applications is the InAs/GaAs QD system [4]- [6][9] [11]. Despite significant progress, the practical potential of the InAs/GaAs QD system isl imited by non-optimized spectral overlap and lower QD absorption [13].…”
Section: Introductionmentioning
confidence: 99%